Making sense of the rural white working class: the contemporary novel of rural retreat and the politics of resentment. Issue 4 (3rd April 2023) - Johansen, Emily
ABSTRACT: A widespread centrist and conservative explanation for the ongoing rise of racist and xenophobic populism has been that progressives have been too preoccupied with identity politics, and not attentive enough to rural economic precarity. This narrative has been particularly popularised in two high-profile memoirs, J.D. Vance's Hillbilly Elegy and Tara Westover's Educated, which both attempt to explain the realities of the rural, white working class and its particular resentments. Simultaneous to the publication of these memoirs, there has been a number of contemporary Anglophone novels about rural retreat published, all of which similarly suggest that rural living offers an alternative or challenge to contemporary life. This paper focuses on two British iterations of this genre, Sarah Moss's Ghost Wall and Fiona Mozley's Elmet, that suggest the rural as a site of communal possibility, rather than a retreat into melancholic resentment. I argue, then, that not only do Ghost Wall and Elmet call into question how a prevailing argument about the current global rise of racist populism is spatialised, but that they frame this as a question that is inextricable from the arrangements of space that structure access to life chances beyond simply those of liberal institutions.